Is Bangladesh's economy approaching the Lewis turning point? - Bairagi, Subir; Kamal, Muntaseer (SAGE Publications, 2019)
During the last decade, Bangladesh economy grew consistently over 6 per cent annually; however, growth rate in the agriculture sector declined. Labour away from agriculture is evident; it is also evident real wages in the agriculture sector are rising. This could be an indication that Bangladesh is moving to a different stage of economic development. This article investigates whether Bangladesh is approaching a stage of economic development where marginal productivity of labour equals its price, called the Lewis turning point (LTP). We find that the reallocation of labour away from agriculture has had a positive but insignificant impact on economic growth in Bangladesh. We also find that the surplus agricultural labour has not fully been absorbed by the economy. Therefore, we conclude Bangladesh has yet to reach the LTP and suggest initiating policies (e.g., job creation in the service sector) that might speed up the country’s movement to the LTP.JEL: O11, O17, O41, O53